Health Education Using Video Media to Improve Parents Knowledge About Handling Choking in Children - Arina, Yevi Asih; Mugianti, Sri; Dewi Rachmawati (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
Choking is an emergency that often occurs in early childhood due to foreign objects or food that block the respiratory tract and can cause death if not treated immediately. This study aims to determine the effect of health education using video media on increasing the knowledge of student guardians about choking management. The study used a pre-experimental one group pretest-posttest design with 34 respondents selected by total sampling at Al-Hidayah Ringinanyar Kindergarten in April-May 2025. The instrument was a choking knowledge questionnaire consisting of 17 items that had been tested for validity (p = 0.005) and reliability (Cronbach's Alpha = 0.82). Data analysis included univariate and bivariate using Wilcoxon test. The results showed that before the intervention 61.8% of respondents had poor knowledge, after the intervention it increased to 88.2% with a good category. The Wilcoxon test resulted in a p value = 0.000 (p < 0.05), which indicates a significant effect after health education with video media. Video media allows respondents to practice the material directly, making it easier to remember and repeat information. In conclusion, health education using video media is effective in increasing the knowledge of student guardians about choking management in early childhood.